2007
DOI: 10.1002/art.22788
|View full text |Cite
|
Sign up to set email alerts
|

Arthritis symptoms, the work environment, and the future: measuring perceived job strain among employed persons with arthritis

Abstract: The findings underscore the diverse areas that contribute to perceptions of job strain and suggest that existing models of job strain do not adequately capture the stress experienced by individuals working with chronic illnesses or the factors associated with job strain. Measures similar to the CIJSS can enhance the tools researchers and clinicians have available to examine the impact of arthritis in individuals' lives.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
55
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 54 publications
(59 citation statements)
references
References 40 publications
4
55
0
Order By: Relevance
“…Additional analyses (data not shown) revealed that the model including presenteeism as an independent variable (AIC 5 359.3) had a higher predicting power than the model excluding presenteeism (AIC 5 379.1). These observations suggest the dominant role of presenteeism over BASFI and BASDAI in predicting sick leave, which is in line with our previously mentioned hypothesis that presenteeism encompasses not only pain, stiffness, and physical functioning, but also depressive symptoms and contextual factors; the latter factors are important determinants of work participation (18,38,39). Since the effects of presenteeism, BASDAI, and BASFI on sick leave are much more pronounced in patients with higher levels (.5) of presenteeism, paying attention to this cohort is important in seeking interventions to reduce sick leave.…”
Section: Discussionsupporting
confidence: 89%
“…Additional analyses (data not shown) revealed that the model including presenteeism as an independent variable (AIC 5 359.3) had a higher predicting power than the model excluding presenteeism (AIC 5 379.1). These observations suggest the dominant role of presenteeism over BASFI and BASDAI in predicting sick leave, which is in line with our previously mentioned hypothesis that presenteeism encompasses not only pain, stiffness, and physical functioning, but also depressive symptoms and contextual factors; the latter factors are important determinants of work participation (18,38,39). Since the effects of presenteeism, BASDAI, and BASFI on sick leave are much more pronounced in patients with higher levels (.5) of presenteeism, paying attention to this cohort is important in seeking interventions to reduce sick leave.…”
Section: Discussionsupporting
confidence: 89%
“…This is a 12-item scale that measures difficulties related to different work activities (e.g., difficulties related to upper and lower extremity mobility) (36,38,39). Responses range from 0 (no difficulty) to 3 (not able to do).…”
Section: Significance and Innovationsmentioning
confidence: 99%
“…This validated 15-item scale of job strain assesses a person's appraisal of the stressfulness of the working environment when living and working with a chronic disease (38). Questions ask about stress related to work and having a chronic disease (e.g., the extent of the stress related to job demands combined with having lupus).…”
Section: Significance and Innovationsmentioning
confidence: 99%
“…Studies suggest that, despite improvements in treatment for rheumatic diseases, many individuals continue to report difficulties working, have elevated absenteeism rates, and report reduced productivity (1)(2)(3)(4). In addition to the physical symptoms of the disease creating difficulties for people in remaining employed, factors like job stress, symptom unpredictability, disruptions to work because of time needed for treatment, and employment factors like a lack of job control and absence of workplace support can create barriers to working (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20).…”
Section: Introductionmentioning
confidence: 99%